The expressions and their products are:
The expressions are given as:
[tex](3d + 2)(d^2 - 1)[/tex]
Open brackets
[tex](3d + 2)(d^2 - 1) = 3d \times d^2 - 3d \times 1 + 2 \times d^2 -2 \times 1[/tex]
Evaluate the products
[tex](3d + 2)(d^2 - 1) = 3d^3 - 3d + 2d^2 -2[/tex]
Rewrite as:
[tex](3d + 2)(d^2 - 1) = 3d^3+ 2d^2 - 3d -2[/tex]
[tex](d - 2)(3d ^2 + 2d + 1)[/tex]
Open brackets
[tex](d - 2)(3d ^2 + 2d + 1) = 3d^3 + 2d^2 + d - 6d^2 - 4d - 2[/tex]
Collect like terms
[tex](d - 2)(3d ^2 + 2d + 1) = 3d^3 + 2d^2 - 6d^2+ d - 4d - 2[/tex]
Evaluate the like terms
[tex](d - 2)(3d ^2 + 2d + 1) = 3d^3 -4d^2 - 3d - 2[/tex]
[tex](3d^2 - 2)(d + 1)[/tex]
Open brackets
[tex](3d^2 - 2)(d + 1) = 3d^3 + 3d^2 -2d - 2[/tex]
Hence, the equivalent expression of (3d^2 - 2)(d + 1) is 3d^3 + 3d^2 -2d - 2
Read more about equivalent expressions at:
https://brainly.com/question/2972832